A comparison between conventional brick and timber-frame brick veneer housing - Mostert, J J J (Department of Civil Engineering, 2020)
Timber-frame brick veneer construction originated in countries in which houses were traditionally constructed with loadbearing timber frames which were clad with non-loadbearing weather boarding or similar light-weight materials. Timber-frame house construction is extensively used in countries such as Canada, Scandinavia, Australia and North America. With the Canadian system, buildings of up to three storeys can be erected with loadbearing timber frames. This particular system was also adopted in France - the Igny project~ and in England - the Harlow project. In most of these cases, basements or crawl-spaces underneath the house were incorporated in the design. In these countries there have a trend towards the use of a brick cladding (veneer) for timber-frame structures. This is a comparatively recent introduction in these countries, but it has already been extensively used. This trend is primarily related to the appearance and other advantages (for example durability and ease of maintenance in the case of a face-brick clauding) of a masonry exterior, while largely retaining the low cost benefits of timber-frame construction.